An improved ZCT-PWM DC-DC converter for high-power and frequency applications - Bodur, H; Bakan, AF (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2004)
In this paper, an improved active resonant snubber cell that overcomes most of the drawbacks of the normal zero-current transition (ZCT) pulsewidth-modulation (PWM) dc-dc converter-is proposed. This snubber cell is especially suitable for an insulated gate bipolar transistor (IGBT) PWM converter at high power and frequency levels. The converter with the proposed snubber cell can operate successfully with soft switching under light-load conditions and at considerably high frequencies. The operation principles, a detailed steady-state analysis, and a snubber design procedure of a ZCT-PWM buck converter implemented with the proposed snubber cell are presented. Theoretical analysis is verified with a prototype of a 5-kW and 50-kHz IGBT-PWM buck converter. Additionally, at 90% output power, the overall efficiency of the proposed soft switching converter increases to about 98% from the value of 91% in the hard-switching case.
Keywords: active snubber cells; soft switching; zero-current switching (ZCS); zero-current transition (ZCT); zero-voltage switching (ZVS); zero-voltage transition (ZVT); CELL; Automation & Control Systems; Engineering; Instruments & Instrumentation